Нейротропные эффекты экстракта альфредии поникшей; Химия растительного сырья; № 4 - Мустафин Р. Н. Рустам Ниязович; Шилова И. В. Инесса Владимировна; Суслов Н. И. Николай Иннокентьевич; Бакибаев А. А. Абдигали Абдиманапович; Медведев Д. М. Дмитрий Михайлович; Дорожко Е. В. Елена Владимировна; Булычева Е. В. Елизавета Владимировна; Черемпей Е. Г. Елена Геннадьевна; Мичурина К. А. Ксения Андреевна (2014, 2014)
Заглавие с экрана